Table of Content - - (Journal of natural sciences, life and applied sciences, 2024)
Table of Content:1. Taxonomic Revision of Hibiscus (Malvoideae) of Malvaceae sensu lato in Toor Al-Baha District, Lahej Governorate, YemenOthman Saad Saeed Al-Hawshabi2. Environmental Impacts of Climate Change: A Comperehensive Review of Causes, Manifestations, and SolutionsSleem Ali Kreba3. Floristic Composition, Life-forms and Chorotypes of Plants for Extended Area from Aqan  to Al-Erais, Lahej Governorate, YemenMazen Alawi Ali Salim Atif, Ahmed Mohammed Moqbal Al-Super, Othman Saad Saeed Al-Hawshabi
Keywords: Journal of Natural Sciences, Life and Applied Sciences